“To be or not to be” located in a cluster?—A descriptive meta-analysis of the firm-specific cluster effect - Nils Grashof; Dirk Fornahl (The Annals of Regional Science, 2021)
In the twenty-first century, clusters can be observed in most developed economies. However, the scientific results regarding the effect of clusters on firm performance are highly contradictive. The inconsistencies in the empirical results make it difficult to infer general conclusions about the firm-specific cluster effect, or in other words, the effect from being located in a cluster on firm performance (e.g. derived through the externalities within clusters). Therefore, this paper aims to reconcile the contradictory empirical findings. It investigates whether the prevalent assumption that clusters are a beneficial location for firms is unconditionally true or whether doubts about the alleged positive effect of clusters on firm performance are justified. By conducting a descriptive meta-analysis of the empirical literature, based on four different performance variables from four separate publication databases, the study investigates the direction of the effect as well as possible moderating influences. We find evidence for a rather positive firm-specific cluster effect. However, we identify several variables from the micro-, meso- and macro-level that directly or interactively moderate the relationship between clusters and firm success. For example, the results demonstrate that a negative firm-specific cluster effect occurs more frequently in low-tech industries than in high-tech industries. “To be or not to be” located in a cluster is therefore not the question, but it rather depends on the specific conditions.
Keywords: L25; O31; O32; R1; 500